Evaluation of Physico-Chemical Properties of Honey Produced in Bale Natural Forest, Southeastern Ethiopia - Bekele Tesfaye; Desalegn Begna; Mitiku Eshetu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2016)
The study was conducted to evaluate the physico-chemical properties of honey from Bale natural forest Southeastern of Ethiopia in 2014/15. For analysis thirty (30) honey samples each of 0.5 to 1 kg were obtained from three locations considering the different agro-ecologies of Bale and compared against to the national and international standards. The physico-chemical characters evaluated were: Color, Moisture Content, Ash, Free Acidity, pH, Hydroxy methyl furfural, Reducing Sugar, Sucrose Content and Electric Conductivity. Though there were some significant variation (P<0.05) between the different agro-ecologies, all samples collected were found in the range of the national and international standard limits. The means value of honey sample collected were Color 92.43 (Amber), Moisture Content (18.80), Ash (0.21), Free Acidity (32.43), pH (3.75), Hydroxy methyl furfural (36.35), Apparent Reducing Sugar (66.41), Sucrose Content (4.48) and Electric Conductivity (0.69). Results obtained in this study, indicate that honeys produced in Bale show excellent quality properties according to the national and international standards.